Perinatal mesenchymal stromal cells of the human decidua restore continence in rats with stress urinary incontinence induced by simulated birth trauma and regulate senescence of fibroblasts from women with stress urinary incontinence - De La Torre, Paz; Pérez-Lorenzo, María Jesús; Alcázar-Garrido, Álvaro; Collado, Jennifer; Martínez-López, Mario; Forcén, Laura; Masero-Casasola, Ana R.; García, Alicia; Gutiérrez-Vélez, Mª Carmen; Medina-Polo, José; Muñoz, Eloy; Flores, Ana I. (Frontiers in Cell and Developmental Biology, 2023)
Stress urinary incontinence (SUI) is a condition that causes the involuntary loss of urine when making small efforts, which seriously affects daily life of people who suffer from it. Women are more affected by this form of incontinence than men, since parity is the main risk factor. Weakening of the pelvic floor tissues is the cause of SUI, although a complete understanding of the cellular and molecular mechanisms of the pathology is still lacking. Reconstructive surgery to strengthen tissue in SUI patients is often associated with complications and/or is ineffective. Mesenchymal stromal cells from the maternal side of the placenta, i.e. the decidua, are proposed here as a therapeutic alternative based on the regenerative potential of mesenchymal cells. The animal model of SUI due to vaginal distention simulating labor has been used, and decidual mesenchymal stromal cell (DMSC) transplantation was effective in preventing a drop in pressure at the leak point in treated animals. Histological analysis of the urethras from DMSC-treated animals after VD showed recovery of the muscle fiber integrity, low or no extracellular matrix (ECM) infiltration and larger elastic fibers near the external urethral sphincter, compared to control animals. Cells isolated from the suburethral connective tissue of SUI patients were characterized as myofibroblasts, based on the expression of several specific genes and proteins, and were shown to achieve premature replicative senescence. Co-culture of SUI myofibroblasts with DMSC via transwell revealed a paracrine interaction between the cells through signals that mediated DMSC migration, SUI myofibroblast proliferation, and modulation of the proinflammatory and ECM-degrading milieu that is characteristic of senescence. In conclusion, DMSC could be an alternative therapeutic option for SUI by counteracting the effects of senescence in damaged pelvic tissue.